Letter to the editor regarding "Covid-19 transmission in fitness centers in Norway - a randomized trial" - Morten Valberg; Jon Michael Gran; Corina S. Rueegg; Marissa LeBlanc (BMC, 2022)
Abstract In a recently published paper in BMC Public Health we read about a randomized trial on Covid-19 transmission performed in five fitness centers in Oslo, Norway, during the spring of 2020. In our opinion, this study has major shortcomings in design and methodology, which have not been addressed by the authors.